Association between B vitamins and schizophrenia: A population-based case-control study. (January 2018) - Cao, Bing; Sun, Xiao-Yu; Zhang, Chuan-Bo; Yan, Jing-Jing; Zhao, Qian-Qian; Yang, Si-Yu; Yan, Lai-Lai; Huang, Ning-hua; Zeng, Jing; Liao, Jie-Ying; Wang, Jing-Yu
Abstract: To explore the association between schizophrenia and six types of B vitamins, including choline, biotin, riboflavin, pyridoxamine, pyridoxine and nicotinamide, based on the hydrophilic interaction liquid chromatography column (HILIC) Liquid Chromatography-Mass Spectrometry (LC-MS) platform. We conducted the case-control study between November 2015 and September 2016 in Weifang, Shandong Province, China. Blood samples from 128 cases of schizophrenia and 101 controls were collected, and B vitamin were measured by LC-MS coupled with HILIC. The HILIC UPLC-MS based analysis of serum B vitamins levels from 128 cases (30 cases with first-episode, 98 cases with relapse) and 101 controls were performed. The results indicated that lower pyridoxine level and schizophrenia was related. (total cases versus controls: β = −0.215, 95% CI: −0.271, −0.125, p < 0.001; first-episode cases versus controls: β = −0.190, 95% CI: −0.277, −0.103, p < 0.001). Higher nicotinamide level was also associated with schizophrenia after adjusting confounders ( β = 0.343, 95% CI: 0.022, 0.664, p = 0.036). Other four B vitamins, including biotin, riboflavin, pridoxamine and choline, were showed no statistically difference in cases versus controls, first episode cases versus relapse cases. Two types of B Vitamins, pyridoxine and nicotinamide, show significant association with the schizophrenia. Highlights: The aim of this study is to investigate the potential association between B vitamins levels and schizophrenia. For better retention and separation of B vitamins, this study was performed based on the HILIC LC-MS platform. The study adjusted the confounding factors that might influence the results including age, sex, BMI, FBG, TG and TC.